Lack of hexose-6-phosphate dehydrogenase impairs lipid mobilization from mouse adipose tissue. - Bujalska, I; Hewitt, K; Hauton, D; Lavery, G; Tomlinson, J; Walker, E; Stewart, P (2008)
In adipose tissue, glucocorticoids regulate lipogenesis and lipolysis. Hexose-6-phosphate dehydrogenase (H6PDH) is an enzyme located in the endoplasmic reticulum that provides a cofactor for the enzyme 11beta-hydroxysteroid dehydrogenase type 1 (11beta-HSD1), regulating the set point of its activity and allowing for tissue-specific activation of glucocorticoids. The aim of this study was to examine the adipose tissue biology of the H6PDH null (H6PDH/KO) mouse. Real-time PCR analysis confirmed similar mRNA levels of 11beta-HSD1 and glucocorticoid receptor-alpha in wild-type (WT) and H6PDH/KO mice in liver and gonadal fat depots. Microsomal 11beta-HSD1 protein levels shown by Western blot analysis corresponded well with mRNA expression in gonadal fat of WT and H6PDH/KO mice. Despite this, the enzyme directionality in these tissues changed from predominately oxoreductase in WT to exclusively dehydrogenase activity in the H6PDH/KO mice. In the fed state, H6PDH/KO mice had reduced adipose tissue mass, but histological examination revealed no difference in average adipocyte size between genotypes. mRNA expression levels of the key lipogenic enzymes, acetyl CoA carboxylase, adiponutrin, and stearoyl-coenzyme A desaturase-2, were decreased in H6PDH/KO mice, indicative of impaired lipogenesis. In addition, lipolysis rates were also impaired in the H6PDH/KO as determined by lack of mobilization of fat and no change in serum free fatty acid concentrations upon fasting. In conclusion, in the absence of H6PDH, the set point of 11beta-HSD1 enzyme activity is switched from predominantly oxoreductase to dehydrogenase activity in adipose tissue; as a consequence, this leads to impairment of fat storage and mobilization.